2010
DOI: 10.1007/s11187-010-9276-5
|View full text |Cite
|
Sign up to set email alerts
|

Drivers of non-profit activity: a cross-country analysis

Abstract: This paper contributes to the existing debate on the determinants of non-profit activity. The main theories have been centered in (1) the study of the individual behavior of people (donors, non-profit entrepreneurs), (2) one single factor or (3) one single country. To quantify this approach, data for 38 countries have been used, extracted from World Values Survey, United Nations Development Program and Global Entrepreneurship Monitor. A structural modeling approach based in partial least squares (PLS) has been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
56
0
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(64 citation statements)
references
References 90 publications
2
56
0
5
Order By: Relevance
“…Although qualitative studies have thus far demonstrated the relevance of 'institutional voids' for entrepreneurial responses (Mair and Marti 2009;Khanna and Palepu 2000), in more recent cross-national empirical work, the relevance of the 'institutional support' mechanism seems to dominate (Nissan et al 2012;Estrin et al 2013;Stephan et al 2014). In this chapter, we focus on the neighbourhood context rather than the (national/regional) context where all formal rules and regulations are enforced.…”
Section: How Does Local Social Capital Relate To Social Entrepreneurimentioning
confidence: 99%
“…Although qualitative studies have thus far demonstrated the relevance of 'institutional voids' for entrepreneurial responses (Mair and Marti 2009;Khanna and Palepu 2000), in more recent cross-national empirical work, the relevance of the 'institutional support' mechanism seems to dominate (Nissan et al 2012;Estrin et al 2013;Stephan et al 2014). In this chapter, we focus on the neighbourhood context rather than the (national/regional) context where all formal rules and regulations are enforced.…”
Section: How Does Local Social Capital Relate To Social Entrepreneurimentioning
confidence: 99%
“…The Failure Thesis and Institutional Void . One of the dominant theoretical perspectives that seeks to explain the size of the nonprofit sector is the government failure thesis (Matsunaga, Yamauchi, and Okuyama ; Nissan, Castaño, and Carrasco ; Salamon, Sokolowski, and Anheier ; Salamon, Sokolowski, and List ; Weisbrod ) . Government failure exists when the government fails to meet public and quasi‐public goods provision and when market imperfections become socially undesirable.…”
Section: Hypotheses Formulationmentioning
confidence: 99%
“…In other words, unattended social needs serve as an opportunity or driver for entrepreneurs to create social value. Although empirical evidence for the failure thesis is weak with respect to the size of the nonprofit sector (Matsunaga, Yamauchi, and Okuyama ; Nissan, Castaño, and Carrasco ; Salamon, Sokolowski, and Anheier ), there is some evidence related to social entrepreneurship. For example, Kerlin () finds that the absence of state social programs relates to the emergence of social enterprise in each of the seven countries that she studies.…”
Section: Hypotheses Formulationmentioning
confidence: 99%
See 1 more Smart Citation
“…They find that the political engagement and the diversity of social networks available in a community have a significant impact on the number of non-profit foundings. Internationally, several studies such as Matsunaga et al (2010), Nissan et al (2010) and Salamon and Anheier (1994) have explained how the size and determinants of the non-profit sectors varies widely by country. These studies however concentrate at the sector level and do not explain what makes an individual non-profit grow.…”
Section: Literature Review Variable Definition and Predictionsmentioning
confidence: 99%